Peran Kurikulum Tersembunyi Pembelajaran Berbasis Alam dalam Membentuk Perilaku Siswa Tata Ruang Sekolah Alam Bengawan Solo Tahun 2018/2019, Distrik Juwiring, Kabupaten Klaten (Studi Fenomenologi) - Zulzil Putriana; Singgih Prihadi; Gentur Adi Tjahjono (GEADIDAKTIKA, 2020)
The research aims to: (1) analysis role of the written curriculum and hidden curriculum natural-based learning in shaping spatial behavior; (2) improvement in student learning outcomes in human material and the environment in shaping spatial behavior; (3) the spatial behavior of students as a result; (4) factors that influence in shaping spatial behavior in the Bengawan School of Nature-School. The study used analysis a mixed method with Sequential Exploratory Design. The data analysis technique used is the Interpretative Phenomenological Analysis, N-Gain analysis, Frequency Distribution analysis,  and Interactive analysis.The result of this research are: (1) The Bengawan School of Nature-School does not have a written curriculum but has a hidden curriculum in the aspects of school establishment goals, contextual learning systems, humanistic learning management, learning independence of students; (2) there is an N-Gain in the increase in pretest learning outcomes with posttest through the Head Number Together intructional model in class VII of 0.387, class VIII 0.667 and class IX of 1; (3) the spatial behavior of SL-SABS students the high category  characteristics through learning with a technical instructional; (4) factors that influence shaping student spatial behavior come from internal factors, namely personal experience and gender, external factors of school institutions in the form of teacher environmental ideology and teacher professionalism, as well as non-school factors namely parent support and online media